2020
DOI: 10.1038/s41418-020-0543-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the autophagic protein ULK1 attenuates axonal degeneration in vitro and in vivo, enhances translation, and modulates splicing

Abstract: Axonal degeneration is a key and early pathological feature in traumatic and neurodegenerative disorders of the CNS. Following a focal lesion to axons, extended axonal disintegration by acute axonal degeneration (AAD) occurs within several hours. During AAD, the accumulation of autophagic proteins including Unc-51 like autophagy activating kinase 1 (ULK1) has been demonstrated, but its role is incompletely understood. Here, we study the effect of ULK1 inhibition in different models of lesion-induced axonal deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 72 publications
(142 reference statements)
5
47
0
6
Order By: Relevance
“…We previously generated and characterized an AAV vector expressing ULK1.DN (AAV.ULK1.DN), resulting in the reduction of endogenous ULK1 levels by ~50%, and analyzed the effects of ULK1 inhibition on neuroprotection 13 , 14 . AAV.ULK1.DN also expresses the fluorescent protein mCherry, which is used to visualize transduced neurons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously generated and characterized an AAV vector expressing ULK1.DN (AAV.ULK1.DN), resulting in the reduction of endogenous ULK1 levels by ~50%, and analyzed the effects of ULK1 inhibition on neuroprotection 13 , 14 . AAV.ULK1.DN also expresses the fluorescent protein mCherry, which is used to visualize transduced neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we showed that ULK1.DN-mediated ULK1 inhibition promoted axonal protection in different models of traumatic axonal lesion, in vitro and in vivo, and that application of the ULK1 inhibitor SBI-0206965 protected axons from degeneration induced by optic nerve crush (ONC) in vivo. Mechanistically, ULK1.DN attenuated autophagy, modulated the differential splicing of degeneration-associated genes and increased translation via an mTOR-mediated mechanism 14 . These findings suggest that ULK1 is a key mediator of axonal degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of excessive autophagy activation by pharmacological intervention has been suggested to be a new tactic to reduce neuronal death ( Lee et al, 2020 ). Compared with the short-term stress responsees such as oxidative stress and apoptosis, autophagy exists in the whole process of SCI ( Cortes et al, 2014 ; He et al, 2016 ; Vahsen et al, 2020 ). Consistently, we found that autophagy-related protein level LC3 II was significantly induced in SCI, and whereas FGF21 attenuated SCI-induced autophagy and improves the functional recovery of SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many studies use α-T172 as a marker for AMPK activity, which can be misleading. For example, the dual AMPK and autophagy initiator ULK1 inhibitor SBI-0206965 counterintuitively induces an increase in α-T172 phosphorylation, possibly due to de-repression of ULK1 negative feedback through this site [ 61 ], while suppressing AMPK signalling [ 81 , 82 ]. This highlights the importance of using downstream AMPK substrates as markers of AMPK activity instead of α-T172 phosphorylation.…”
Section: Regulation By Phosphorylationmentioning
confidence: 99%